Computer-based learning objects in healthcare: the student experience - Blake, Holly (De Gruyter, 2010)
Web-based computer learning objects, such as Reusable Learning Objects (RLOs), are becoming more commonplace in nursing and medical education. However, evaluation of RLOs specifically has been limited. The aim of the study was to determine how RLOs impact on the student learning experience and to compare the use and evaluation of RLOs by nursing and medical students. An online questionnaire survey was completed by 233 students (163 nursing and 73 medical). RLOs were more commonly used by nursing students than medical students. Students in both disciplines valued RLOs for flexibility of learning, as revision aids, and to supplement classroom-based learning. Nursing and medical students have different learning needs, and developing materials at the right level of learning is important. Barriers to the use of RLOs included lack of IT competence, technical difficulties, and lack of staff awareness of computer-based learning aids.